Gestão de crises como gestão da identidade: o lugar do discurso e da imagem - Lemos, Felipe Diemer de (2018)
The current job environment, coming from the Semiotics according to Peirce, and the Semiotic of culture, it analyzes the activity in the organizational crisis management, related to the identity management. Through this perspective, the identity management in an organization that was analyzed by the Seventh Day Adventist Church it is understood as a product or result of the interactions between the organization discourse, the perceived image, and the organizational crisis, once they are part of it, also, the process of organizational identity structure. In this way, the research forms a theoretical relationship between the crisis management and the organizational identity management. In this research, it was possible to see the identity of an organization is also built by the crisis phenomena in the media, in which they create an impact, not only in the speech produced by the organization, but also in the image perceived by the different publics that relate to it. The organizational crises show, therefore, that they are not obstacles to the organization’s development, but they are elements capable of, inevitably, taking the organization (and hence, are part of it) to think in its own way of being, and expressing itself.